2011
DOI: 10.1017/s0021932011000721
|View full text |Cite
|
Sign up to set email alerts
|

Secular Changes in Height, Body Weight, Body Mass Index and Pubertal Development in Male Children and Adolescents in Krakow, Poland

Abstract: This study examined the secular changes in height, body weight, body mass index and pubertal development in male children and adolescents in Krakow (Poland) over the past 80 years, with an emphasis on the last decade (2000-2010). The survey of the population of Krakow is a continuation of observations conducted in that area for many years. The analysis aims to determine whether in the last decade Krakow still witnessed the secular trend, and what form the trend took. The body height and weight, and body mass i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
32
0
5

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 43 publications
5
32
0
5
Order By: Relevance
“…Also, this declining trend is similar with the male puberty development in other countries, but the pace is faster. One study in Poland reported an over 3-month decrease between 2000 and 2010 in the age of initial appearance of pubic hair in boys (12). Another study in Thailand showed that the age at testicular enlargement Tanner exposures, which may be related to the trend of earlier pubertal onset (26)(27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, this declining trend is similar with the male puberty development in other countries, but the pace is faster. One study in Poland reported an over 3-month decrease between 2000 and 2010 in the age of initial appearance of pubic hair in boys (12). Another study in Thailand showed that the age at testicular enlargement Tanner exposures, which may be related to the trend of earlier pubertal onset (26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…The sampling procedure, as previously described in detail (18)(19), was the same at all CNSSCH time points. The participants were primary and high school boys aged [7][8][9][10][11][12][13][14][15][16][17][18] years from the same areas in each province. All subjects were selected by stratified cluster sampling, in that sampling took place in classes randomly selected from each grade in the selected school.…”
Section: Subjectsmentioning
confidence: 99%
“…[51] oraz Krysta i wsp. [52]. Chrzanowska i Suder [49] Legenda do 100 osób -żółty; 100-500 osób -niebieski; 500-1000 osób -zielony; 1000-5000 osób -czerwony; pow.…”
Section: Stan Badań W Analizowanym Okresieunclassified
“…Analogiczne badania zostały przeprowadzone przez Krysta i wsp. [52] wśród krakowskich dzieci i młodzieży płci męskiej (1862 chłopców w wieku 3,5-18,5 roku), które dowiodły, że w ciągu ostatnich 80 lat, a zwłasz-cza w ostatniej dekadzie (2000-2010), nastąpił wzrost średniej masy ciała i BMI przy braku wzrostu wysokości ciała. Ponadto, zaobserwowano przyśpieszone dojrzewanie chłopców.…”
Section: Stan Badań W Analizowanym Okresieunclassified
“…Previous studies suggest that improvement in socioeconomic status, change in diet and nutrition, and considerable medical developments, which translate into better medical care and better hygienic and sanitary conditions (14) , constitute an important cause of secular changes (15) . Positive correlations between BMI and height have been described before (2) .…”
mentioning
confidence: 99%